Rheumatoid Factor as a Potentiator of Anti-Citrullinated Protein Antibody-Mediated Inflammation in Early Undifferentiated Seronegative Osteoarthropathy - Spasovski, Dejan; Genadieva-Stavric, Sonja; Sotirova, Tatjana; Brezovska-Kavrakova, Julijana (Makedonski medicinski pregled, 2017)
To compare the values and accuracy of the test in anticyclic citrullinated peptides antibodies, rheumatoid factor (RF), C-reactive protein (CRP) and disease activity index in early diagnosis of untreated psoriatic arthritis (PsA). Using the ELISA method of DIA-STAT Anti CCP (Axis-Shield Diagnostics), sera of 70 participants were examined (35 untreated patients with PsA and 35 subjects from the healthy control group). RF and CRP were determined with the agglutination test (latex test). At the same time the sensitivity, specificity, predictive value for positive and negative testsand accuracy were determined. Of 35 patientswith PsA, 1 patient showed presence of anti-CCP antibodies (sensitivity test 2.86%), while RF was foundin 0 patients(sensitivity test 0%). In the healthy control group positivevalues for RF, CRP and erythrocyte sedimentation rate were detected in 1 patient. ACPA antibodies have low sensitivity, but high specificity in PsA.